Effect of High Incubation Temperature on the Blood Parameters of Layer Chicks - Sgavioli,S (2016)
ABSTRACT Adequate environmental temperature control is essential for incubation efficiency. Layer breeder eggs (n=360) were weighed and distributed in a completely randomized experimental design with two treatments, consisting of two incubation temperatures (T1=37.5 °C, control; and T2=39.0 °C, hot), with two incubators per temperature, and 90 eggs per incubator, totaling 360 eggs. Hatchability, embryo mortality, and chick cloacal and body surface temperatures were not affected by incubation temperature. Eggs incubated at the hot temperature presented greater egg mass loss and higher eggshell conductance than those incubated at the control temperature. Layer chicks derived from eggs incubated at control temperature showed greater absolute weight, yolk-free egg mass, and heavier hearts than those from eggs submitted to heat stress during incubation. The control group presented lower base excess and ionized calcium blood levels. Incubating eggs at temperatures higher than those recommended compromises body and heart development of layer chicks and negatively affects blood ionized calcium availability, and therefore, bone mineralization during embryo development. Efficient temperature control during the incubation of fertile eggs is essential to obtain good quality layer chicks.